Intraperitoneal Dissemination of Endometrial Cancer Cells After Hysteroscopy: A Systematic Review and Meta-Analysis. Issue 2 (1st February 2010) - Polyzos, Nikolaos P.; Mauri, Davide; Tsioras, Spyridon; Messini, Christina I.; Valachis, Antonis; Messinis, Ioannis E.
Abstract : Introduction: Hysteroscopy is a diagnostic procedure with a high accuracy in diagnosing endometrial cancer. Because of the increase of intrauterine pressure during distention media inflation, several retrospective studies postulated that it may result in cancer cell dissemination within the peritoneal cavity through the fallopian tubes. We therefore set to estimate whether hysteroscopy increases the risk for intraperitoneal cancer cell dissemination in patients with endometrial cancer and the risk of disease upstaging in patients with clinically early-stage disease. Methods: We searched the PubMed, the ISI Web of Science, and the Cochrane Library through July 2009. Eligible trials were all controlled clinical trials in which patients were allocated to hysteroscopy (alone or after other diagnostic procedure, eg, dilation and curettage and biopsy) versus any other diagnostic procedure except hysteroscopy or no procedure before surgery for endometrial carcinoma. Results: Nine trials were included in our analysis. One thousand fifteen patients with histologically proven endometrial carcinoma were allocated to hysteroscopy or no hysteroscopy before surgery. Hysteroscopy resulted in a significantly higher rate of malignant peritoneal cytology (odds ratio [OR], 1.78; 95% confidence interval [CI], 1.13-2.79; P = 0.013) and significantly higher disease upstaging owing solely to the presence of malignant cells in the peritoneal cavity (OR, 2.61; 95% CI, 1.47-4.63; P = 0.001) compared with no hysteroscopy. When isotonic sodium chloride was used as distention medium, hysteroscopy resulted in a statistically significant higher rate of malignant peritoneal cytology (OR, 2.89; 95% CI, 1.48-5.64; P = 0.002), whereas a nonsignificant trend for higher malignant cells was observed in patients allocated to the hysteroscopy group (OR, 3.23; 95% CI, 0.94-11.09; P = 0.062) when inflated media pressure reached or exceeded 100 mm Hg. Conclusions: Hysteroscopy in patients with endometrial cancer hints a risk for cancer cell dissemination within the peritoneal cavity. Prospective and sufficiently powered trials are needed to clarify whether the risk of cancer cell spreading is correlated with worse prognosis.